Socio-philosophical analysis of the Michel Foucault’s work “The birth of the clinic” - Kawtar, Z. (Запорізький державний медико-фармацевтичний університет, 2023)
The aim. Considering this the aim of the abstract is to analyze and reveal the peculiarities and main aspects of the emergence of the modern medical profession that would influence on the further history of medicine and society in general.
Keywords: тези доповідей